Evaluation of Acute and Subchronic Oral Toxicity of Copra Meal Hydrolysate: A Novel Candidate for Prebiotic in Sprague Dawley Rats - Jiraporn Tangthong; Francis Ayimbila; Massalin Nakphaichit; Suttipun Keawsompong (Journal of Toxicology)
Copra meal hydrolysate (CMH) with high protein and mannooligosaccharides (MOS) was derived by β-mannanase hydrolysis. CMH has been shown to elicit health benefits via prebiotic properties. However, a systematic examination of its safety is required before effective utilization. This study assessed CMH oral acute toxicity at a single dose of 2000 mg/kg for 14 consecutive days, while a subacute toxicity test was conducted by daily oral administration of CMH at doses of 0.25, 0.5 and 1.0 mg/kg for 90 days using Sprague Dawley rats and following OECD guidelines 423 and 408. The acute toxicity study showed that the LD50 of CMH was over 2000 mg/kg since no mortality or abnormal clinical signs were observed at this dose. The subacute toxicity results showed that CMH did not induce any abnormalities in body weight, food and water consumption, clinical signs, haematology, clinical chemistry, organ weight and necropsy. Significant changes in some of the parameters were observed but most were not treatment-related and had no effect on animal health. No toxicity-related microscopic findings were recorded in the examined tissues (lung, heart, liver, spleen and kidneys). Oral administration of CMH had a ‘no observed adverse effect level (NOAEL)’ of 1.0 mg/kg for both male and female Sprague Dawley rats. CMH demonstrated a high level of safety in animal studies and can be considered a safe prebiotic substance for use in the food and nutraceutical industries.